Qualidade da água em viveiros de criação de peixes com sistema de fluxo contínuo - Macedo, Carla Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2004)
This study was carried out at six semi-intensive breeding fishponds at the UNESP (CAUNESP) Aquaculture Center, in Jaboticabal, SP. The fishponds were set up sequentially, with the water from one fishpond flowing directly into the neat one, with no previous treatment, receiving water from other tanks and smaller ponds from the pisciculture, frogbreeding, and crustacean-breeding sectors. The purpose of this work was to determine, physical and chemical variables (pH, dissolved oxygen, conductivity, temperature, total alkalinity, and inorganic carbon forms), nutrients (nitrogen and phosphorous), heavy metals (lead, cadmium, copper, zinc, manganese, nickel, and chromium), solids in suspension, DBO5, DQO, sanitary relevant microorganisms (coliforms and heterotrophic bacteria), and planktonic community consist, in order greater information on the cultivation system dynamics and impact minimizing alternatives. Collections were made at the inlet of each pond for fifteen days, at two different times of the year, the dry and the wet periods. The results demonstrated that the sequential layout of the fishponds studied had favored a change in the limnological features along the system; the differences found between the periods were related to the variables directly connected to climate factors; the microbiological parameters have displayed a great inflow of fecal coliforms, total coliforms and heterotrophic bacteria in the last fishpond, from which the water flows to a natural stream. Environmental management practices are recommended, with the construction of biofilters on the effluent of these fishponds as well as appropriate food management not accumulating an excess of food not assimilated by the fish, in the water column

O estudo foi realizado em seis viveiros de criação semi-intensiva de peixes do Centro de Aqüicultura da UNESP (CAUNESP), Jaboticabal, SP. Os viveiros apresentaram-se dispostos em série onde a água de um viveiro passou diretamente para o outro, sem nenhum tratamento prévio, recebendo ainda água de outros tanques e viveiros em paralelo dos setores de piscicultura, ranicultura e carcinicultura. O trabalho verificou a influência do sistema no aumento das concentrações de nutrientes, dos parâmetros limnológicos, microbiológicos e do plâncton de um para o viveiro subseqüente. Foram analisadas variáveis físicas e químicas (pH, oxigênio dissolvido, condutividade, temperatura, alcalinidade total e formas de carbono inorgânico), nutrientes (nitrogênio e fósforo), metais pesados (chumbo, cádmio, cobre, zinco, manganês, níquel e cromo), sólidos em suspensão, DBO5, DQO, densidade de microrganismos de significado sanitário (coliformes e bactérias heterotróficas) e composição da comunidade planctônica. As coletas foram realizadas na entrada de cada viveiro durante quinze dias em duas épocas do ano, seca e chuva. A distribuição em série dos viveiros estudados favoreceu um aumento nas variáveis limnológicas ao longo do sistema, assim como as diferenças observadas entre os períodos estiveram relacionadas somente às variáveis relacionadas aos fatores climáticos. Os coliformes fecais, totais e bactérias heterotróficas foram mais elevados no período de chuva devido principalmente às altas temperaturas e à entrada pelas águas de escoamento. Os resultados obtidos possibilitam a recomendação de práticas de manejo ambiental, o desvio do efluente dos tanques em paralelo e um manejo alimentar adequado, minimizando o desperdício de ração não assimilada pelos peixes
Keywords: Aquicultura; Peixe - Criação; Viveiros; Limnologia; Água - Qualidade; Fishes